Sora: high-performance software radio using general-purpose multi-core processors - Tan, Kun; Liu, He; Zhang, Jiansong; Zhang, Yongguang; Fang, Ji; Voelker, Geoffrey M. (Communications of the ACM, 2011)
This paper presents Sora, a fully programmable software radio platform on commodity PC architectures. Sora combines the performance and fidelity of hardware software-defined radio (SDR) platforms with the programmability and flexibility of general-purpose processor (GPP) SDR platforms. Sora uses both hardware and software techniques to address the challenges of using PC architectures for high-speed SDR. The Sora hardware components consist of a radio front-end for reception and transmission, and a radio control board for high-throughput, low-latency data transfer between radio and host memories. Sora makes extensive use of features of contemporary processor architectures to accelerate wireless protocol processing and satisfy protocol timing requirements, including using dedicated CPU cores, large low-latency caches to store lookup tables, and SIMD processor extensions for highly efficient physical layer processing on GPPs. Using the Sora platform, we have developed a few demonstration wireless systems, including SoftWiFi, an 802.11a/b/g implementation that seamlessly interoperates with commercial 802.11 NICs at all modulation rates, and SoftLTE, a 3GPP LTE uplink PHY implementation that supports up to 43.8Mbps data rate.